Self-efficacy in patients with breast cancer: A health belief model approach - Mutia Nadra Maulida; Putri Widita Muharyani; Antarini Idriansari; Karolin Adhisty (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Breast cancer is a disturbance in the growth of normal breast cells characterized by abnormal cells arising from normal cells that can infiltrate lymphatic tissue and blood vessels. This will have a major impact on patients and their families, both physically, psychologically, economically and in other aspects of life which certainly affect the patient's self-efficacy about their own ability to carry out healthy behaviors that have an impact on their treatment. One of the support efforts that can be given is the intensification of activities through the Health Belief Model.Purpose: To determine the effect of Self-efficacy in patients with breast cancer: A health belief model approachMethod: The design used in this study was a quasi-experimental design with one group pretest-posttest. Determination of the sample by purposive sampling method as many as 60 participants. Data was collected using a self-efficacy questionnaire.Results: The Marginal homogeneity test obtained a p-value = 0.001, which means that there is an effect of giving interventions with the Health Belief Model on self-efficacy in breast cancer patients.Conclusion: Intervention with the Health Belief Model approach can increase the self-efficacy of breast cancer patients who are undergoing treatment.